2016
DOI: 10.1145/2897824.2925967
|View full text |Cite
|
Sign up to set email alerts
|

Motion graphs for unstructured textured meshes

Abstract: Scanned performances are commonly represented in virtual environments as sequences of textured triangle meshes. Detailed shapes deforming over time benefit from meshes with dynamically evolving connectivity. We analyze these unstructured mesh sequences to automatically synthesize motion graphs with new smooth transitions between compatible poses and actions. Such motion graphs enable natural periodic motions, stochastic playback, and user-directed animations. The main challenge of unstructured sequences is tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 35 publications
0
36
0
Order By: Relevance
“…Optical flow Though initially proposed for aligning images [LK81], optical flow has been extended to the sphere [YSV*10] and more general surfaces [PKC*16]. These extensions formulate the brightness constancy constraint in terms of local tangent spaces and iteratively update the deformation by using temporally varying tangent vectors fields and exponentiation to parametrize the change in deformation.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Optical flow Though initially proposed for aligning images [LK81], optical flow has been extended to the sphere [YSV*10] and more general surfaces [PKC*16]. These extensions formulate the brightness constancy constraint in terms of local tangent spaces and iteratively update the deformation by using temporally varying tangent vectors fields and exponentiation to parametrize the change in deformation.…”
Section: Related Workmentioning
confidence: 99%
“…Using the approach of Prada et al . [PKC*16], we find W⃗ hierarchically by using the Lie‐derivative on 0‐forms to linearize advection:…”
Section: Our Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…Gauss map diffusion (or spherical harmonic flow) is discussed in [PKC*16], and normal field filtering is also exploited in [Tau01, YOB02, TWBO02, TWBO03, SRML07, ZFAT11]. However, they are only used in the application of mesh smoothing and denoising.…”
Section: Related Workmentioning
confidence: 99%
“…Sequential methods for frame-to-frame temporal coherence are prone to errors due to drift and rapid motion [6,46]. Previous work [54] has shown that semantic tracklets improve segmentation for single view video.…”
Section: Semantic Trackletsmentioning
confidence: 99%